If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7v + 12b = 694 Reorder the terms: 12b + 7v = 694 Solving 12b + 7v = 694 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-7v' to each side of the equation. 12b + 7v + -7v = 694 + -7v Combine like terms: 7v + -7v = 0 12b + 0 = 694 + -7v 12b = 694 + -7v Divide each side by '12'. b = 57.83333333 + -0.5833333333v Simplifying b = 57.83333333 + -0.5833333333v
| X-4x-7=5x(x+21) | | 2(7-2n)=87 | | a*4+8=11 | | 5+x+x+3=32 | | 12x+26=6x+116 | | 5+0.05x= | | d-1.9=9.1 | | 36=-4v | | 10m-22=68 | | 7+12z-5=9z+42-7z | | (x+2)(3x-2)=28 | | 3a+2b=29+a+b | | 4x^2+5x+1=52 | | 43-3x=1x+9 | | -9+x=x | | 3y-9=-6x | | 0.7(x+10)+0.1x=23 | | 8(3x-5)=60+20x | | 1-2n+4=19 | | 3ln(x+2.8)=4.8 | | 85y-47=y-(-89) | | 49+l=74 | | 36+p=81 | | 3(x+7)+4=3x+25 | | 5(3x-4)=7(2x-3) | | n+4=1-n | | 3(x+4)+7=3x+19 | | (x+745)+x+(x-301)=6360 | | (3x+2)=(4x-3) | | 62.9296(x)+(64.9278)(1-x)=63.546 | | 3(x+7)+4=3x+3 | | z^2-(1+i)z+(2+2i)=0 |